Improved thermal-electrical-optical model and performance assessment of a PV-blind embedded glazing façade system with complex shading effects. (1st December 2019) - Luo, Yongqiang; Zhang, Ling; Su, Xiaosong; Liu, Zhongbing; Lian, Jinbu; Luo, Yongwei
Highlights: A dynamic shadow model was established for the façade. Improved model of PV-blind façade was established and experimentally validated. The system shadow distributions and shading coefficient maps are formulated. "U", "M", "Λ", and "W" shaped error curves are identified. Impact of façade configurations and geographical locations are revealed. Abstract: PV-blind embedded glazing façade is a promising façade system with multi-function of flexible daylighting control, power generation and heat gain/loss reduction. It is investigated in some studies before, but usually for model simplification, the building shadow is not considered, even it is not clear how the building shadow affects simulation accuracy and system performance. In this study, an improved thermal-electrical-optical model is proposed with full consideration of dynamic complex shading effects from building eave, window frame and PV-blinds. A series of experimental tests are conducted to verify the system model. The newly proposed model is used as an important tool to better understand impacts of complex shading effects. The results show some new and valuable findings: (a) The radar map of shading coefficient is rotating clockwise with increased local latitude and it is shifting from west to east with increased local longitude, which is in accordance with the varied local longitude; (b) The "U", "M", "Λ", and "W" shaped error curves are, for the first time, identified in simulation if the complex shading effects are not considered and the annual simulation errors are about 40–120% for optical model, 12.5–27% for thermal model and as high as 10–18 times for electrical model; (c) The power generation and thermal performance are greatly affected by façade orientations and blind arrangements. And when the PVBGF system is applied to cities in different zones, the overall system performance is heavily sensitive to the local latitude than local longitude.